THE EFFECT OF EMPLOYEE WELL-BEING AND WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE THROUGH WORK ENGAGEMENT , WITH PERCEIVED ORGANIZATIONAL SUPPORT AS A MODERATING VARIABLE (A Case Study of Employees at PT. Saranajaya Serbaguna Malang) - Salsabila Citra Devi; Budi Eko Soetjipto; Madziatul Churiyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the influence of employee well-being and work-life balance on employee performance through work engagement , and examine the role of perceived organizational support as a moderating variable in the relationship between work engagement and employee performance . This study uses a quantitative approach with a descriptive and explanatory research design . The study population was 260 production employees of PT. Saranajaya Serbaguna Malang, with a sample of 156 respondents selected using proportionate stratified random sampling . Data were collected through a closed questionnaire based on a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0.9.9. The results showed that employee well-being and work-life balance had a positive and significant effect on employee performance and work engagement . Furthermore, work engagement was proven to have a positive and significant effect on employee performance . Mediation findings showed that work engagement partially mediated the influence of employee well-being and work-life balance on employee performance . In addition, perceived organizational support was proven to strengthen the relationship between work engagement and employee performance . Theoretically, this study extends the application of Social Exchange Theory to the context of the automotive component manufacturing industry in Indonesia. Practically, the results emphasize the importance of human resource management strategies focused on well-being, work-life balance, work engagement, and organizational support to improve production employee performance.